A modal analysis based on reactive power compensation on 6-bus Oman electrical grid - Adnan Saif Al Mamari; Siti Fauziah Toha; Salmiah Ahmad; Ali Salim Al Mamari (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
This paper covers the modal analysis application (MATLAB 2019a) for improving the voltage profiles by optimum positioning of the capacitor banks for 6-bus Oman Electrical System because the Oman electricity TransmissionCompany (OETC) is suffering of drop voltage in these 6 buses especially during summer season as a peak period. The Newton-Raphson (N-R) method will help to determine the required reactive power for each load bus and as well the ideal position or point of capacitors. The process aims to maintain the Q-V relations of the electrical grid by correlating the lowest Eigen-values to related Eigen-vectors in obtained Jacobian matrix. It depends on the Eigen-values, if they are positive then the system’s voltage is stable otherwise it is not stable. In a stable system, the potential voltage collapse could be anticipated by checking the participation factors for a group of minimal positive Eigen-values. In general, the critical weak bus is associated with lowerEigen-values. Electrical system collapse is attributable to the weakest bus in the network and it could be avoided by determining the weak buses and providing capacitor banks at suitable locations which will lead to improve the voltage stability margin.